Conhecido, assenhoreado, criado e conduzido pelo SENHOR: um estudo exegético do Sl 139 - Nyékplola, Gbedey Mébounou (2013)
This thesis is a study on Psalm 139. The principal aim of the research is to present the image of God transmitted by this poem and investigate how mankind, created and known by God can relate to his experience of faith with the struggle for survival in this world, marked by people who insist on injustice and violence due to their wickedness. In order to justify the research on psalm 139, the Hebrew text was chosen, since it is the language in which the text was originally composed. By so doing the guarantee of being close to the first meaning of the text is more assured. Particularly being a language that lays emphasis, on knowledge of other important parallels in the whole canon of the Scriptures, especially other writings (books) that form the Hebrew Bible. In the light of what has been stated above, the Hebrew Concordance of Old Testament has become the most important research tool. Always attentive to the literary-stylistic dimensions of Psalm 139, the study aims to describe the theological dimensions of this biblical prayer. The research progresses along the verses and stanzas that compose the poem, commenting word by word, sentence by sentence and stanza by stanza. Psalm 139 meditates on human existence as determined by God. For someone who feels unjustly treated and threatened in his life. It is interesting to see from this biblical poem, the divine omniscience, omnipresence, divine omnipotence and God's creative act; God, the good shepherd and liberator. This religious perspective offers hope because at the long run GOD is aware of all life experience: being omniscient, powerful and the one who liberates mankind from all sort of danger and slavery